A fluorescein-based chemosensor for relay fluorescence recognition of Cu(ii) ions and biothiols in water and its applications to a molecular logic gate and living cell imaging. Issue 19 (5th April 2017) - Fu, Zhen-Hai; Yan, Lu-Bin; Zhang, Xiaolong; Zhu, Fan-Fan; Han, Xin-Long; Fang, Jianguo; Wang, Ya-Wen; Peng, Yu
Abstract : Relay recognition of copper(ii ) ions and biothiols via a fluorescence "on–off–on" cascade has been realized in 100% aqueous solution when excited by the visible light. Abstract : Relay recognition of copper(ii ) ions and biothiols via a fluorescence "on–off–on" cascade was designed and realized as a new sequential combination of cations and small molecules. Probe1 bearing a fluorescein skeleton was thus synthesized, which performed well in 100% HEPES buffer (pH = 7.0) solution, as a highly sensitive, selective fluorescence sensor for Cu 2+ . The limit of detection (LOD, 0.017 ppm) was obtained, and this value is much lower than 1.3 ppm, allowed by US EPA. The 1 : 1 complex generated from fast sensing of Cu 2+ when excited at 491 nm, showed good relay recognition for biothiols ( i.e., Cys, Hcy and GSH with low detection limits of 0.12 μM, 0.036 μM and 0.024 μM, respectively) via remarkable fluorescence enhancement. The origin of this relay process was disclosed through ESI-MS and corresponding density functional theory (DFT) computations. Notably, probe1 can be utilized for the construction of a molecular logic gate with the IMPLICATION function by using the above fluorescence changes. Moreover, this relay recognition was also applied to HepG2 cell imaging successfully.